The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1098/rspa.2019.0838
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of root reinforcement in soils: an experimental methodology using four-dimensional X-ray computed tomography and digital volume correlation

Abstract: Vegetation on railway or highway slopes can improve slope stability through the generation of soil pore water suctions by plant transpiration and mechanical soil reinforcement by the roots. To incorporate the enhanced shearing resistance and stiffness of root-reinforced soils in stability calculations, it is necessary to understand and quantify its effectiveness. This requires integrated and sophisticated experimental and multi-scale modelling approaches to develop an understanding of the processes at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…After DVC processing, full-field data containing displacements, normal strain and shear strain components were post-processed using a custom MATLAB script. A study was carried out to optimize the DVC sub-volume size for reliable correlation, error caused by noise, strain measurement accuracy and spatial resolution [21]. This found that it was necessary to correlate adjacent scans in the XCT dataset (rather than e.g.…”
Section: (C) Dvcmentioning
confidence: 99%
See 2 more Smart Citations
“…After DVC processing, full-field data containing displacements, normal strain and shear strain components were post-processed using a custom MATLAB script. A study was carried out to optimize the DVC sub-volume size for reliable correlation, error caused by noise, strain measurement accuracy and spatial resolution [21]. This found that it was necessary to correlate adjacent scans in the XCT dataset (rather than e.g.…”
Section: (C) Dvcmentioning
confidence: 99%
“…The minimum subset size achievable was 32 pixels cubed, and for subsets of this size noise was found to accumulate linearly with the number of displacement steps in the sequence, with the largest strain standard deviation reaching 38 millistrain at the end of the test. The subset size and noise sensitivity study is described in detail in [21]. The 75% overlap in the subset size meant that displacement was calculated on a three-dimensional grid of eight pixels or 0.37 mm.…”
Section: (C) Dvcmentioning
confidence: 99%
See 1 more Smart Citation
“…The first set of data consisted of laboratory direct shear tests on soil reinforced by juvenile willow, gorse and festulolium grass grown under laboratory conditions (Liang et al 2017), Bull et al (2020). In the following, first author initials 'TL' and 'DB' are used to differentiate tests conducted by Liang et al and Bull et al.…”
Section: Experimental Data Sourcesmentioning
confidence: 99%
“…To capture the behavior of soil and soil-root interactions, it is necessary to obtain deformation information from the bulk of the soil (Bull et al, 2020). Advanced experimental methods using imaging techniques (e.g., X-ray Computed Tomography (XCT) or time lapse synchrotron X-ray Computed Tomography (4D CT)) have been shown to work well for capturing three-dimensional information of soils and roots (Perret et al, 2007;Peth et al, 2010;Keyes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%